Effect of lime and gypsum on calcium and aluminum amounts of the compacted layer of a Dark Red Latosol - Borges, Elias Nascentes; Laforga, Gilmar; Lana, Regina M. Quintão; Borges, Eloá V. Silva; Costa, Liovando Marciano da (Pesquisa Agropecuaria Brasileira, 1997)
This study was conducted at the laboratory of the Universidade Federal de Uberlândia, MG state, Brazil, to evaluate the influence of soil compaction and different gypsum + lime levels on some chemical properties of the compacted layer. Three overlapping PVC rings formed a column with external soil layers of 0.5 dm depth without compaction, and the central ring consisted of a layer with different compaction levels. Treatments were conducted in a factorial arrangement with three liming (0.0; 2.031 and 4.062 t ha-1), five gypsum (0.0; 0.508; 1.016; 1.524 and 2.032 t ha-1), and five compaction (1.10; 1.25; 1.40; 1.55 and 1.70 kg dm-3) levels. It was observed that both compaction and gypsum levels increased Ca2+ levels and reduced Al3+ levels. However, these effects depended on liming levels combined with gypsum.